Observation of the decay B0s to φπ+π- and evidence for B0 to φπ+π- - Harnew, N; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Hill, D; Jalocha, P; John, M; Lupton, O; Malde, S; Nandi, A; Topp-Joergenson, S; et al. (American Physical Society, 2017)
The first observation of the rare decay B0s to φπ+π- and evidence for B0 to φπ+π- are reported, using pp collision data recorded by the LHCb detector at centre-of-mass energies √s = 7 and 8 TeV, corresponding to an integrated luminosity of 3fb^-1. The branching fractions in the π+π- invariant mass range 400 < m(π+π-) < 1600 MeV/c2 are [3.48 ± 0.23 ± 0.17 ± 0.35] X 10^-6 and [1.82 ± 0.25 ± 0.41 ± 0.14] X 10^-7 for B0s to φπ+π- and B0 to φπ+π- respectively, where the uncertainties are statistical, systematic and from the normalisation mode B0s to φπ+π-. A combined analysis of the π+π- mass spectrum and the decay angles of the final-state particles identifies the exclusive decays B0s to φf0(980), B0s to φf2(1270), and B0s →ϕρ0 with branching fractions of [1.12 ± 0.16^+0.09-0.08 ± 0.11] X 10^-6, [0.61 ± 0.13^+0.12-0.05 ± 0.06] X 10^-6 and [2.7 ± 0.7 ± 0.2 ± 0.2] X 10^-7, respectively.